Efeitos da interação e toxicidade das proteínas Cry1 e Vip3A de Bacillus thuringiensis em Diatraea saccharalis (Fabr., 1794) (Lepidoptera: Crambidae) - Davolos, Camila Chiaradia [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The aim of this research was to evaluate the toxicity of different Cry1 and Vip3A proteins from Bacillus thuringiensis to Diatraea saccharalis, verify the proteins binding to receptors of the target insect and to analyze the protein interactions in larval control, seeking information to support safe and sustainable the use of transgenic Bt plants. The most toxic protein assayed was Cry1Ab followed by Cry1Ac, Vip3Aa, Cry1Ca and Cry1Fa. The population tested was not susceptible to Cry1Ea protein. Cry1Aa showed very low toxicity. Biotinylated Cry1 proteins showed specific binding to the midgut brush border membrane vesicles of the larvae. Heterologous competitive binding assays suggested a model of three receptors, a common receptor for Cry1Aa and Cry1Ab another one for Cry1Fa and Cry1Ab. Vip3Aa did not compete for binding with any of the Cry proteins tested. Among interactions bioassays, the combinations between Cry1Ab:Cry1Ca and Cry1Fa:Cry1Ca showed synergistic effect, whereas the other combinations showed antagonistic effects

O presente trabalho objetivou avaliar a toxicidade de diferentes proteínas Cry1 e Vip3Aa de Bacillus thuringiensis em larvas de Diatraea saccharalis, verificar o modo de união dessas proteínas aos receptores do inseto alvo e analisar a interação dessas proteínas no controle larval, buscando informações para subsidiar o uso de plantas geneticamente modificadas com genes cry1 e vip3Aa de forma segura e duradoura. A análise de suscetibilidade larval revelou a proteína Cry1Ab como mais efetiva no controle, seguida das proteínas Cry1Ac, Vip3Aa, Cry1Ca e Cry1Fa. A população testada não foi suscetível à proteína Cry1Ea. A proteína Cry1Aa apresentou baixa toxicidade. Nos ensaios de união específica, as proteínas Cry1 ligaram-se a receptores presentes no intestino médio de D. saccharalis e um modelo com três diferentes receptores foi proposto com base nos ensaios de competição heteróloga. Um receptor comum para Cry1Aa, Cry1Ab e Cry1Ac, outro para Cry1Fa e Cry1Ab e um receptor diferente para a proteína Vip3Aa. Dentre as interações avaliadas por bioensaios, as combinações proteicas: Cry1Ab:Cry1Ca e Cry1Fa:Cry1Ca apresentaram efeito sinérgico; as demais combinações revelaram efeitos antagônicos
Keywords: Broca da cana-de-açúcar; Pragas agricolas - Controle; Proteinas de bacterias; Genetica vegetal; Testes biologicos; Bacterial proteins